2004
DOI: 10.1183/09031936.04.00009704
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of the use of PCR assay in diagnosing pulmonary TB in a low-incidence area

Abstract: Economic evaluation of the use of PCR assay in diagnosing pulmonary TB in a low-incidence area. I. Rajalahti, E-L. Ruokonen, T. Kotomäki, H. Sintonen, M.M. Nieminen. #ERS Journals Ltd 2004. ABSTRACT: To determine whether polymerase chain reaction (PCR) testing in the initial diagnosis of pulmonary tuberculosis (TB) is cost-effective in a low-prevalence population, an economic evaluation was carried out between the smear and culture (NOPCR) and smear, culture and PCR (zPCR) strategies.A decision tree model base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…A conventional PCR result will most often be available within 2 days; thus, the benefit of allowing discontinuation of isolation on the basis of single-sputum PCR results is a reduction of the time spent in isolation for patients who do not have contagious tuberculosis. Previously, PCR-based isolation decision models with fast-access PCR (Xpert RIF/MTB) were found cost-effective [21,27,28]. One study using a conventional PCR technique (Cobas Amplicor; Roche Diagnostics) [29] did not find this cost-effectiveness, mainly because PCR was performed only twice weekly and on all samples.…”
Section: Discussionmentioning
confidence: 99%
“…A conventional PCR result will most often be available within 2 days; thus, the benefit of allowing discontinuation of isolation on the basis of single-sputum PCR results is a reduction of the time spent in isolation for patients who do not have contagious tuberculosis. Previously, PCR-based isolation decision models with fast-access PCR (Xpert RIF/MTB) were found cost-effective [21,27,28]. One study using a conventional PCR technique (Cobas Amplicor; Roche Diagnostics) [29] did not find this cost-effectiveness, mainly because PCR was performed only twice weekly and on all samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recalculated from the detailed unit costs given for 2000, the mean costs for a 6-month treatment, which comprised of inpatient stays of only 14 days, amounted to J6673.10 per drug-susceptible TB case [40].…”
Section: Finlandmentioning
confidence: 99%
“…In the selection process 4278 citations and 241 websites were identified, of which only 12 scientific articles [35][36][37][38][39][40][41][42][43][44][45][46] and two websites [47,48] were eligible for final inclusion, as they contained specific information on at least one of the cost components as listed above. To take into consideration the gaps in gross domestic product (GDP) per capita between the 27 present EU member countries, we presented separately the results for the EU-15 states (member countries of the EU prior to the accession of 12 candidate countries on May 1, 2004 comprising the following 15 countries: Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Luxembourg, Netherlands, Portugal, Spain, Sweden and the UK) and the other 12 countries that have since joined (table 1 shows figures of total treatment costs and table 2 shows the key features of all 12 studies included in our review).…”
Section: Direct Costsmentioning
confidence: 99%
“…Our data represent the experience of a single institution with a moderate annual prevalence of TB cases. Previous cost-effectiveness analyses have shown that routine use of NAA tests is more cost-effective in settings with high prevalence of TB and smearpositive cases (23,24), but performance in lower prevalence areas should still benefit from reducing hospitalization costs. The use of two different NAA tests in our study can be considered as another limiting factor of our study.…”
Section: Discussionmentioning
confidence: 99%